Bridging Before and After: Library Science’s Soviet Legacy in Ukraine - Haigh, Maria (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l'ACSI, 2013)
My paper examines the current state of library and information science in Ukraine, framing this in the context of its historical legacy as a part of the former Soviet Union. It is based on extensive research using Ukrainian, English and Russian sources as well as considerable time spent observing conditions in Ukraine and interviewing local librarians and information science educators across the country as part of my Fulbright fellowship there. Cet article examine l'état actuel de la bibliothéconomie et des sciences de l'information en Ukraine, dans le contexte de l'héritage historique de cette ancienne république soviétique. Mes travaux se basent sur une recherche exhaustive de sources en ukrainien, en anglais et en russe, ainsi que sur de nombreuses d'heures d'observation des conditions en Ukraine et d'entrevues avec des bibliothécaires et des éducateurs en sciences de l'information de partout au pays. Cette étude est rendue possible grâce à une bourse de recherche de la Fondation Fulbright.